Alternative herbal medicine for acne treatment (Research, Society and Development, 2021)
Acne is considered a chronic skin inflammation that affects young people and adults of different age groups. Its etiology is multifactorial and triggers from mild lesions to comedogenic lesions that can cause scars that are sometimes unsightly. Conventional therapies have several limitations, expanding the search for those affected by alternative therapies. Alternative medicine is based on the use of medicinal plants and their derivatives and has been used frequently in acne. The aim of the present work is to analyze how phytotherapy can help in the alternative treatment of acne. Thus, a comprehensive bibliographic search was carried out on the Scielo, PubMed, Science Direct and Scholar Google platforms with research between the years 2010 to 2020. Of the 250 articles selected according to the subject's applicability, 30 were used for this review. The research result showed a diversity of medicinal plants with significant potential in the treatment of acne, among them Camellia sinensis, Orthosiphon stamineus and Rosmarinus officinalis. The plants with potential to act in the treatment of acne presented bioactive compounds such as the polyphenol Epigallocatechin-3-gallate, Strictinina, Aloemodina, Crisopanol and Aloína, which play activity in the different pathophysiology of acne, and can be an alternative treatment for acne in relation to conventional therapies.